2008
DOI: 10.1080/02640410802298268
|View full text |Cite
|
Sign up to set email alerts
|

Practical precooling: Effect on cycling time trial performance in warm conditions

Abstract: The purpose of this study was to compare the effects of two practical precooling techniques (skin cooling vs. skin + core cooling) on cycling time trial performance in warm conditions. Six trained cyclists completed one maximal graded exercise test (VO2(peak) 71.4 +/- 3.2 ml x kg(-1) x min(-1)) and four approximately 40 min laboratory cycling time trials in a heat chamber (34.3 degrees C +/- 1.1 degrees C; 41.2% +/- 3.0% rh) using a fixed-power/variable-power format. Cyclists prepared for the time trial using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 31 publications
10
73
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21] Direct comparisons with the magnitude of ergogenic effect observed in previous studies are limited because authors of only 2 studies 3,4 used the same protocol as we did, and only Kay et al 4 used the same mode of exercise. Kay et al 4 observed a 6.0% (900 m) improvement in performance when using an identical exercise protocol after 60 minutes of coolwater immersion, and Booth et al 3 observed a 4.2% improvement in distance run in 30 minutes after 60 minutes of coolwater immersion.…”
Section: Precooling Effectmentioning
confidence: 79%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20][21] Direct comparisons with the magnitude of ergogenic effect observed in previous studies are limited because authors of only 2 studies 3,4 used the same protocol as we did, and only Kay et al 4 used the same mode of exercise. Kay et al 4 observed a 6.0% (900 m) improvement in performance when using an identical exercise protocol after 60 minutes of coolwater immersion, and Booth et al 3 observed a 4.2% improvement in distance run in 30 minutes after 60 minutes of coolwater immersion.…”
Section: Precooling Effectmentioning
confidence: 79%
“…Although these improvements are slightly higher than our findings, our effect does fall within the range of improvement commonly observed for self-paced exercise performance after precooling. 11,15,16,19 For example, Arngrimsson et al 16 observed a 1.1% (13-second) improvement in running time (approximately 19 minutes) for 5 km when participants wore cooling vests during a 38-minute warmup. Quod et al 19 observed a 3.8% (42-second) improvement in time to complete a fixed amount of work during self-paced cycling (approximately 18 minutes) when exercise was preceded by 30 minutes of coolwater immersion and 40 minutes of wearing a cooling vest before a 20-minute warmup.…”
Section: Precooling Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that maintaining a favorable core to skin thermal gradient, independent of lowering T c before exercise, can positively impact performance. In contrast, another study showed that when applying different cooling procedures prior to a 40-min cycling time trial in the heat, only the procedure (water immersion followed by ice vest) which reduced T c sk and had no effect on performance (Quod et al, 2008) sk per se did not affect intensity during a 7.5-km cycling time trial (Levels et al, 2012). However, wearing a cooling vest and refrigerated band around the head -sk but not T c and improved 20-min cycling time trial performance in a hot and humid environment (29 °C, ~ 80% relative humidity) by an average increase in power output of 17 W compared to control (Gonzales et al, 2014).…”
Section: Precoolingmentioning
confidence: 97%
“…Lowering the initial T c sk ) prior to exercise via precooling has been shown to enhance exercise time to exhaustion (Lee & Haymes, 1995;González-Alonso et al, 1999;Uckert & Joch, 2007) and distance covered in a given period of time (Booth et al, 1997;Kay et al, 1999;Quod et al, 2008) under hot conditions. Some investigators have speculated that a high critical T c (~ 40 °C) is a major limiting physiological factor related to impaired performance in hyperthermia, regardless of the baseline T c at the start of exercise (González-Alonso et al, 1999) and the rate of T c rise (MacDougall et al, 1974).…”
Section: Introductionmentioning
confidence: 99%